Perlindungan Hukum Bagi Investor pada Perseroan Terbatas yang Pailit Saat Pandemi Covid-19 - Galuh Meidella Nastiti (CV. Syntax Corporation Indonesia, 2021)
The study discussed legal protections for investors whose limited liability companies were insolvent during the COVID-19 pandemic. the type of research used in this study is normative by using data sources, namely books - literature books and applicable laws. In this study, using qualitative data analysis method by collecting data that is then processed into a research result. The results of the study can be concluded that investors become concurrent creditors in obtaining compensation or fulfillment of their rights at a time when limited liability companies are insolvent during the covid-19 pandemic. This suggests that protections for investors whose limited liability companies were insolvent during the COVID-19 pandemic are lacking and there are no clear legal guarantees to protect investors.